Maintenance planning in wind farms with allocation of teams using genetic algorithms - Fonseca, Inacio; Torres Farinha, Jose; Maciel Barbosa, Fernando (Revista IEEE América Latina, 2014)
Renewable energy is essential for global sustainability. Wind power has given a great contribution to this energy paradigm. The paper describes a maintenance management system for inshore and offshore wind farms, as well as a method to schedule maintenance using genetic algorithms. Under this subject there exists a sub-problem that concerns with the determination of the cheapest path between two points. The paper compares the performance of three methods: genetic algorithms, Dijkstra's algorithm and ant optimization algorithm to the determination of the cheapest path between different wind parks for maintenance.